Optical thin films and coatings : from materials to applications - Piegari, Angela; Flory, François (Woodhead Publishing Limited, 2018)
Annotation Optical thin film coatings improve the performance of optical systems and most modern optical systems could not function without them. Examples of optical thin film coatings are mirrors, anti-reflection coatings, beamsplitters, and filters. These are used in a diverse range of applications including telecommunications, displays and lighting, architectural glass and automotive glass. Part one introduces the design and manufacturing of optical thin film coatings. Part two covers characterization and modelling of optical thin film coatings. Part three looks at novel materials for optical thin film coatings. Part 4 provides extensive coverage of applications of optical thin film coatings.
Keywords: Optical films.; Optical coatings.; Thin films -- Optical properties.; elektronické knihy; electronic books